Public Library, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
Exterior view of the Public Library corner Pembroke and Knox streets, Port of Spain, Trinidad. There are two persons pushing a cart on the road.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Library buildings--Trinidad and Tobago; [1910]; Cities and towns--Trinidad and Tobago--Port of Spain; Library architecture--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Libraries--Trinidad and Tobago; Public libraries--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fences--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago